Menganalisis Faktor dan Upaya Pencegahan Kekerasan dalam Rumah Tangga: Studi Kasus Panca Darmansyah - Jenniviera, Johana; Maryam, Salsabilla; Hosnah, SH. MH, Dr. Asmak Ul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Domestic violence (DV) is a complex social issue with widespread impacts. The case of Panca Darmansyah, who murdered his four children, highlights the high level of extreme domestic violence, triggered by gender inequality, economic pressure, and emotional incapacity. This study analyzes the causes of DV, law enforcement responses, and preventive measures against fatal violence. Despite the existence of regulations such as Law No. 23 of 2004, inadequate legal responses exacerbate the situation. Preventing DV requires a holistic approach, including gender equality education, psychological support, and mental health evaluations of perpetrators. This research recommends strengthening law enforcement mechanisms and early interventions to protect victims and prevent further violence